Evaluation of different health education interventions among preschoolers: A randomized controlled pilot trial - B J John; S Asokan; S Shankar (Wolters Kluwer Medknow Publications, 2013)
Objective: The aim of this study is to assess the impact of three different health education methods among preschoolers. Study Design: The study group included 100 preschoolers of the same socio-economic status randomly selected and divided into four groups. Debris index (DI-S) was recorded for all children followed by the dental health education. Group A received dental health education from the Dentist; Group B from the class teacher trained by the Dentist and Group C from the dental residents dressed mimicking cartoon characters. Group D acted as the control group. Post-intervention evaluation program was carried out after 3 months. Data were analyzed by Chi-square test, paired t-test and analysis of variance (ANOVA) appropriately using the SPSS Version 17.1. Results: Comparison of pre- and post-intervention data showed that there was a statistically significant improvement in the (DI-S) scores in all groups except the control group. Group C showed a significant improvement compared to the other Groups A, B, and D (P < 0.04). Conclusion: Drama as a method of health education can have a bigger impact on the oral health attitude and practices of the preschoolers. These modes can serve to reinforce as well as improve the oral health practices among pre-school children.